Dengeki Daisy. Vol. 15 - Motomi, Kyousuke (Shojo beat manga., 2014)
"Teru gets kidnapped, and Kurosaki rushes to find out where she's being held. The search takes him to an uninhabited island where Akira is determined to find 'M's Last Testament.' With the entire island rigged to blow up, will Kurosaki save both Teru and Akira in time?"--Page 4 of cover.